2018
DOI: 10.3390/ijms19020437
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior of Surfactant on Lignite Surface: A Comparative Experimental and Molecular Dynamics Simulation Study

Abstract: Experimental and computational simulation methods are used to investigate the adsorption behavior of the surfactant nonylphenol ethoxylate (NPEO10), which contains 10 ethylene oxide groups, on the lignite surface. The adsorption of NPEO10 on lignite follow a Langmuir-type isotherm. The thermodynamic parameters of the adsorption process show that the whole process is spontaneous. X-ray photoelectron spectroscopic (XPS) analysis indicates that a significant fraction of the oxygen-containing functional groups on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 34 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…One study in humans showed that GPR39 levels were significantly reduced in the hippocampus and cortex of suicide victims (45). The highest levels of Zn 2ϩ in the body are in the prostate and seminal fluid (46), and GPR39 is differentially expressed in normal versus malignant prostate cells, where it regulates cell growth and proliferation (10,12,13), potentially contributing to the association with benign prostate hyperplasia observed in the present work. Finally, the observation that individuals heterozygous for rare variants in GPR39 have a significant association with diseases of hair and hair follicles should be considered in light of a recent study that found that GPR39 marks a class of stem cells in the sebaceous gland and contributes to wound healing in mice (47).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…One study in humans showed that GPR39 levels were significantly reduced in the hippocampus and cortex of suicide victims (45). The highest levels of Zn 2ϩ in the body are in the prostate and seminal fluid (46), and GPR39 is differentially expressed in normal versus malignant prostate cells, where it regulates cell growth and proliferation (10,12,13), potentially contributing to the association with benign prostate hyperplasia observed in the present work. Finally, the observation that individuals heterozygous for rare variants in GPR39 have a significant association with diseases of hair and hair follicles should be considered in light of a recent study that found that GPR39 marks a class of stem cells in the sebaceous gland and contributes to wound healing in mice (47).…”
Section: Discussionsupporting
confidence: 50%
“…Many of the GPCRs have no known agonist, and their dominant signaling pathways have not been characterized (Table 1). We therefore chose to focus on GPR39, the Zn 2ϩ receptor, which has been characterized in cellular and knockout mouse models and for which both agonist and dominant signaling pathways are known (12,13).…”
Section: Missense and Synonymous Variants Alter Gpcr Function Gpr39 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The different adsorption behavior of collectors on the surface of Bulianta coal will affect the diffusion behavior of water molecules on the surface of coal. This diffusion behavior can be reflected by the mean square displacement (MSD) and diffusion coefficient (d) of water molecules on (modified) coal surface [ 31 , 32 , 33 ].…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The adsorption of collectors on the sub-bituminous coal surface will affect the diffusion behavior of water molecules on the coal surface, which can be reflected by the mean square displacement (MSD) and the self-diffusion coefficient (D). MSD can quantify the diffusion strength of the water molecule on the coal surface with time [28][29][30]:…”
Section: Mobility Of Water Molecules Before and After The Adsorption Of Collectorsmentioning
confidence: 99%